Saxo og Rigsdagen i Besançon: »Da han (Octavian) var færdig, sagde kejseren, at det var for at gøre ende på denne strid, at han havde kaldt alle provinsernes konger sammen til denne drøftelse og at det efter hans mening ikke ville være rigtigt at modsætte sig deres afgørelse.« - Pajung, Stefan; Liljefalk, Lone (Kirkehistoriske Samlinger, 2006)
This article deals with the Imperial Diet at Besançon in the beginning of September 1162 and Saxo’s account. The purpose of the diet at Besançon was the Emperor Frederick Barbarossa’s intention to solve the papal schism between Alexander III and Fredericks own candidate Victor IV Saxo is the most important source that deals with the diet, yet it must not entirely be taken for face value. This is mainly due to the fact that Saxo has his own agenda, and has »edited« his own version of the events. Saxo uses a lot of effort to depict his king as being the victim of the Emperors deceit - Valdemar the Great is described as the ideal »rex iustus« while the Emperor is the incarnation of the »rex tyrannus«. In reality the Danish delegation had its own agenda, in which the schism only played a minor part. After the Emperor’s conquest and sacking of Milan it must have appeared wise to the Danish king to swear the promised oath of fealty to the Emperor, who was at the height of his powers. At the same time the diet was a perfect opportunity to improve diplomatic relations with the neighbouring German princes in order to be able to deal with Norway and the Wendish tribes. The main problem with Saxo’s account is that it lacks any reference to the general political situation in Europe, the negotiations between the Emperor and the French king Louis VII or the imperial triumphs in Italy. Most importantly he simplifies the frontlines drawn by the schism. According to him it would seem that the Empire was a monolithic structure, where the Emperor was able to command everyone, clergyman and layman, to do his bidding and support him in his backing of Victor IV. Nothing could be further from the truth. The Empire was deeply divided, a conglomerate of different territories and bishoprics with widely diverging agendas. Bishops in the Empire could be staunch supporters of the imperial cause, either because they were imperial puppets or because they genuinely believed that Victor IV was the true pope. They could be traditional Augustinians who supported a balance between regnum et sacerdotium, but some were adamant in their support of Alexander III. When it comes to the fringes ofthe Empire, the Emperor could rally less and less support. This is very clear when it comes to the kingdom of Burgundy, but also in Italy only the bishops situated closest to subjugated Milan supported the Emperor openly. Apart from Denmark, ofthe European countries only Bohemia backed the imperial cause. The weakness of the imperial position became apparent already shortly after the diet when important bishoprics fell from the imperial cause and in 1165 the Emperor had to use force in order to secure the necessary support for the new antipope Paschalis III. In Saxo’s account we only meet a threatening Emperor and a schismatic German clergy - the reality was far more complex.